Simulation and Experimental Studies of a New Defected Ground Structure for Microstrip Lines at Ka-band - Dixit, Rajendra Prasad; Roy, Rajesh; Kush, Abhimanyue Kumar; Sharma, Kiran (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*320.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942666);" role="presentation">Simulation <span dir="ltr" style="left: calc(var(–scale-factor)*119.30px); top: calc(var(–scale-factor)*320.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*137.18px); top: calc(var(–scale-factor)*320.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932495);" role="presentation">experimental results of a <span dir="ltr" style="left: calc(var(–scale-factor)*242.09px); top: calc(var(–scale-factor)*320.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912046);" role="presentation">new <span dir="ltr" style="left: calc(var(–scale-factor)*262.01px); top: calc(var(–scale-factor)*320.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972024);" role="presentation">type of <span dir="ltr" style="left: calc(var(–scale-factor)*294.53px); top: calc(var(–scale-factor)*320.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923387);" role="presentation">Defected Ground Structure <span dir="ltr" style="left: calc(var(–scale-factor)*408.07px); top: calc(var(–scale-factor)*320.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942);" role="presentation">(DGS) <span dir="ltr" style="left: calc(var(–scale-factor)*438.34px); top: calc(var(–scale-factor)*320.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*453.46px); top: calc(var(–scale-factor)*320.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945935);" role="presentation">microstrip <span dir="ltr" style="left: calc(var(–scale-factor)*497.86px); top: calc(var(–scale-factor)*320.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964898);" role="presentation">line at <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954207);" role="presentation">Ka-<span dir="ltr" style="left: calc(var(–scale-factor)*86.90px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874197);" role="presentation">band <span dir="ltr" style="left: calc(var(–scale-factor)*109.70px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.882551);" role="presentation">have been <span dir="ltr" style="left: calc(var(–scale-factor)*154.10px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.864894);" role="presentation">discussed. <span dir="ltr" style="left: calc(var(–scale-factor)*198.53px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903643);" role="presentation">The proposed <span dir="ltr" style="left: calc(var(–scale-factor)*257.57px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950499);" role="presentation">modified <span dir="ltr" style="left: calc(var(–scale-factor)*296.83px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.857358);" role="presentation">square <span dir="ltr" style="left: calc(var(–scale-factor)*326.35px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945013);" role="presentation">slot DGS <span dir="ltr" style="left: calc(var(–scale-factor)*367.39px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935538);" role="presentation">exhibits <span dir="ltr" style="left: calc(var(–scale-factor)*402.43px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912553);" role="presentation">single <span dir="ltr" style="left: calc(var(–scale-factor)*429.70px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888096);" role="presentation">stop <span dir="ltr" style="left: calc(var(–scale-factor)*449.86px); top: calc(var(–scale-factor)*333.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930103);" role="presentation">band in frequency <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*347.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.865441);" role="presentation">range <span dir="ltr" style="left: calc(var(–scale-factor)*96.74px); top: calc(var(–scale-factor)*347.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945286);" role="presentation">from 26 <span dir="ltr" style="left: calc(var(–scale-factor)*131.42px); top: calc(var(–scale-factor)*347.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944892);" role="presentation">GHz <span dir="ltr" style="left: calc(var(–scale-factor)*152.90px); top: calc(var(–scale-factor)*347.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931408);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*163.34px); top: calc(var(–scale-factor)*347.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929344);" role="presentation">40 GHz. Th<span dir="ltr" style="left: calc(var(–scale-factor)*211.25px); top: calc(var(–scale-factor)*347.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914887);" role="presentation">ere are many published works on DGS up to K-<span dir="ltr" style="left: calc(var(–scale-factor)*402.67px); top: calc(var(–scale-factor)*347.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911639);" role="presentation">band but DGS performance in <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*360.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954207);" role="presentation">Ka-<span dir="ltr" style="left: calc(var(–scale-factor)*86.90px); top: calc(var(–scale-factor)*360.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922561);" role="presentation">band has to be explored. Thus, stop <span dir="ltr" style="left: calc(var(–scale-factor)*237.17px); top: calc(var(–scale-factor)*360.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930979);" role="presentation">band effect of a new DGS has been studied <span dir="ltr" style="left: calc(var(–scale-factor)*420.22px); top: calc(var(–scale-factor)*360.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*435.34px); top: calc(var(–scale-factor)*360.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962077);" role="presentation">microstrip line at <span dir="ltr" style="left: calc(var(–scale-factor)*508.54px); top: calc(var(–scale-factor)*360.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954207);" role="presentation">Ka- <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*373.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878941);" role="presentation">band. V<span dir="ltr" style="left: calc(var(–scale-factor)*105.50px); top: calc(var(–scale-factor)*373.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934112);" role="presentation">ariation <span dir="ltr" style="left: calc(var(–scale-factor)*140.30px); top: calc(var(–scale-factor)*373.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946305);" role="presentation">in DGS dimensions changes the <span dir="ltr" style="left: calc(var(–scale-factor)*279.41px); top: calc(var(–scale-factor)*373.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.882277);" role="presentation">stop <span dir="ltr" style="left: calc(var(–scale-factor)*300.43px); top: calc(var(–scale-factor)*373.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911454);" role="presentation">band characteristics. <span dir="ltr" style="left: calc(var(–scale-factor)*388.03px); top: calc(var(–scale-factor)*373.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*407.95px); top: calc(var(–scale-factor)*373.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909787);" role="presentation">simulated <span dir="ltr" style="left: calc(var(–scale-factor)*451.18px); top: calc(var(–scale-factor)*373.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918742);" role="presentation">results have been <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915561);" role="presentation">validated <span dir="ltr" style="left: calc(var(–scale-factor)*111.62px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946098);" role="presentation">with the <span dir="ltr" style="left: calc(var(–scale-factor)*147.14px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.859303);" role="presentation">measured <span dir="ltr" style="left: calc(var(–scale-factor)*188.21px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.858337);" role="presentation">data. <span dir="ltr" style="left: calc(var(–scale-factor)*210.29px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904046);" role="presentation">Resonant frequency of s<span dir="ltr" style="left: calc(var(–scale-factor)*307.99px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921929);" role="presentation">top <span dir="ltr" style="left: calc(var(–scale-factor)*323.71px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874197);" role="presentation">band <span dir="ltr" style="left: calc(var(–scale-factor)*345.91px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91543);" role="presentation">of the DGS can be <span dir="ltr" style="left: calc(var(–scale-factor)*423.82px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917069);" role="presentation">varied <span dir="ltr" style="left: calc(var(–scale-factor)*451.66px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971512);" role="presentation">from <span dir="ltr" style="left: calc(var(–scale-factor)*473.74px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907581);" role="presentation">28.2 <span dir="ltr" style="left: calc(var(–scale-factor)*494.26px); top: calc(var(–scale-factor)*386.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946521);" role="presentation">GHz to <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*400.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905081);" role="presentation">35.4 <span dir="ltr" style="left: calc(var(–scale-factor)*92.18px); top: calc(var(–scale-factor)*400.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93967);" role="presentation">GHz.